Going Underground: Bootlegging and Individual Innovative Performance - Criscuolo, Paola; Salter, Ammon; Ter Wal, Anne L. J. (Organization Science, 2014)
To develop innovations in large, mature organizations, individuals often have to resort to underground, “bootleg” research and development (R&D) activities that have no formal organizational support. In doing so, these individuals attempt to achieve greater autonomy over the direction of their R&D efforts and to escape the constraints of organizational accountability. Drawing on theories of proactive creativity and innovation, we argue that these underground R&D efforts help individuals to develop innovations based on the exploration of uncharted territory and delayed assessment of embryonic ideas. After carefully assessing the direction of causality, we find that individuals’ bootleg efforts are associated with achievement of high levels of innovative performance. Furthermore, we show that the costs and benefits of bootlegging for innovation are contingent on the emphasis on the enforcement of organizational norms in the individual’s work environment; we argue and demonstrate empirically that the benefits of an individual’s bootlegging efforts are enhanced in work units with high levels of innovative performance and which include members who are also engaged in bootlegging. However, during periods of organizational change involving formalization of the R&D process, individuals who increase their bootlegging activities are less likely to innovate. We explore the implications of these findings for our understanding of proactive and deviant creativity.